DIFFERENTIATION BETWEEN POSITIVE AND NEGATIVE EMOTINS USING PUPIL DIAMETER - BABIKER, AREEJ BABIKER IDRIS (2014)
This dissertation is introducing an optimized emotion recognition system using individual's pupil diameter through experimental study. Pupil diameter is one of the physiological signals that are used to recognize emotions. It was chosen to reduce time required for emotion identification and to minimize system cost because it doesn't require attachment of external devices unlike other physiological signals e.g. Electroencephalogram (EEG).